PRINSIP KEHATI-HATIAN DALAM PERBANKAN DAN AKAD MURABAHAH - Rimarshanda Anugrahita; Baidhowi Baidhowi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Islamic banking, as an integral part of the national financial system, possesses distinctive characteristics that differentiate it from conventional banking, particularly in its adherence to the principles of Islamic law. One of the fundamental principles that must be upheld by Islamic financial institutions is the prudential principle. This principle serves not only as a risk control mechanism but also as a reflection of the moral and legal responsibilities of financial institutions toward their customers and society at large. This paper aims to examine the implementation of the prudential principle within Islamic banking contracts, particularly in murabahah financing contracts, and to explore the urgency of legal protection for customers as the more vulnerable party in contractual relationships. The research applies a normative juridical approach by analyzing relevant legislation and combining it with conceptual and philosophical insights, particularly Gustav Radbruch’s theory of justice, which emphasizes legal certainty, justice, and utility. The findings reveal that although prudential principles are formally regulated, the practical application still presents potential imbalances and vulnerabilities for customers. Therefore, the prudential principle must be implemented substantively through transparent, accountable, and consumer-oriented governance. Consistent and comprehensive application of the prudential principle will not only strengthen public trust in Islamic financial institutions but also serve as a vital foundation for the stability and sustainability of the Islamic banking sector in Indonesia.